Speaking Christian : why Christian words have lost their meaning and power-- and how they can be restored - Borg, Marcus J. (New York : HarperCollins, 2011)
Asserts that a failure to understand Christian words and phrases has lead to the religion losing much of its meaning, and offers a path back to a true understanding of Christianity.
Speaking Christian -- Beyond literalism -- Salvation -- The Bible -- God -- God's character -- Jesus -- The death of Jesus -- Easter -- Believing and faith -- Mercy -- Righteousness -- Sin -- Forgiveness and repentance -- John 3:16 -- Born again -- The only way -- The ascension -- Pentecost -- The rapture and the second coming -- Heaven -- The creeds and the Trinity -- The Lord's Supper -- The Lord's prayer -- Conclusion.
Includes bibliographical references (p. [241]-243).
Keywords: Theology, Doctrinal -- Study and teaching; Christian education and language; Christianity -- Doctrines -- Study and teaching; Christian education